An analysis of core–mantle boundary related seismic waves using full-waveform modelling and adjoint methods. Issue 2 (6th October 2022) - Koroni, Maria; Borgeaud, Anselme; Fichtner, Andreas; Deschamps, Frédéric
SUMMARY: The core–mantle boundary (CMB) is the most abrupt internal discontinuity in the Earth, marking the solid–fluid boundary between mantle and outer core that strongly affects the dynamics of the Earth's interior. However, good agreement between models of CMB topographic variations is still lacking. This is probably due to difficulties relating to observations on seismograms and to the lack of good models of lowermost mantle velocity structure. Using spectral-element synthetic seismograms and adjoint methods, we perform traveltime analyses of seismic waves interacting with the CMB. We focus on reflected and refracted P and S waves. We select some of the most important and routinely used seismic phases: ScS, SKS, SKKS, PcP, PKP, PKKP and PcS, given their path through mantle and core and their interaction with the CMB. These seismic waves have been widely deployed by seismologists trying to image CMB topography and lowermost mantle structure. To analyse the reliability of measuring their traveltimes to infer CMB topography, we perform experiments in two ways. First, we compute synthetic seismograms with a dominant period of T ≈ 11s, for computational efficiency, using existing models of CMB topography. We compare traveltime perturbations measured by cross-correlation on the synthetics to those predicted using ray theory. We find deviations from a perfect agreement between ray theoretical predictions of time shifts and those measured on synthetics with and without CMB topography. Second, we calculate Fréchet sensitivity kernels of traveltimes with respect to shear and compressional wave speeds. We also explicitly compute boundary sensitivities with respect to the CMB interface. We observe that the overall sensitivity of the traveltimes is mostly due to volumetric velocity structure and that imprints of CMB on traveltimes are less pronounced. Our study explains the observed difficulties relating to inferring CMB topography using traveltimes and provides a suite of finite frequency sensitivity kernels computed with the adjoint method. The kernels allow us to qualitatively explain the behaviour of measured traveltimes and understand the trade-off between velocity and CMB topography. They can also serve as reference of finite frequency effects on traveltimes of observed seismic phases. From our analyses we conclude that: i) traveltime anomalies measured on S waves are more in accord with ray theoretical predictions, ii) PcP, PKP, ScS and SKS phases have more pronounced sensitivity to the boundary and iii) separating the greater effects of velocity from those due to the boundary structure is difficult, as they intricately affect the traveltime. We propose that jointly inverting for CMB topography and lowermost mantle velocity structure using full-waveform synthetics and adjoint sensitivity kernels can progress our understanding of deep Earth structure and finite frequency effects on observed waveforms.